2017
DOI: 10.1038/s41598-017-00349-8
|View full text |Cite
|
Sign up to set email alerts
|

Fgf21 regulates T-cell development in the neonatal and juvenile thymus

Abstract: We have previously shown that Fibroblast growth factor 21 (Fgf21) is expressed in the thymus as well as in the liver. In line with this expression profile, Fgf21 was recently reported to protect against ageing-related thymic senescence by improving the function of thymic epithelial cells (TECs). However, the function of Fgf21 in the juvenile thymus remained to be elucidated. We investigated the physiological roles of Fgf21 in the juvenile thymus and found that young Fgf21 knockout mice, but not β-Klotho knocko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…Our results from plasma IgG, IgM and IgA concentrations in the reference group at days 14 and 21 showed that only IgA increased at the end of the suckling period, in agreement with the findings from other studies [ 45 ]. It is known that newborn rodents during the first week of life produce antibodies depending on Th2 responses, in contrast to adult rats, which show a Th1 response [ 49 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results from plasma IgG, IgM and IgA concentrations in the reference group at days 14 and 21 showed that only IgA increased at the end of the suckling period, in agreement with the findings from other studies [ 45 ]. It is known that newborn rodents during the first week of life produce antibodies depending on Th2 responses, in contrast to adult rats, which show a Th1 response [ 49 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies also described a decrease in T cell percentage after EGF supplementation to preterm rats over 17 days [ 62 ]. Regarding FGF21, other studies did not provide comparative information; only a study contradictory to ours was found, which showed that 1- and 4-week-old FGF21-knockout mice exhibited lower percentages of CD4 + and CD8 + splenic cells, with a thymus-independent action also suggested [ 45 ]. These and other results counteracting the age-related evolutionary pattern also suggested an intriguing hypothesis, reflecting the importance of these factors maintaining immaturity rather than inducing it, which could be of importance during this particular period.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Physiologically, FGF-21 is reported to be expressed from tissues involved in metabolism such as the liver, adipose tissues, skeletal muscle, and pancreas [9]. Secreted FGF-21 could regulate whole-body metabolism via its impact on the function of several tissues including brain and adipose tissues in an endocrine manner [10]. In white adipocytes, FGF-21 stimulates glucose uptake in an insulin-independent manner, modulates lipolysis and enhances mitochondrial oxidative capacity, and potentiates PPARγ activity [11].…”
Section: Introductionmentioning
confidence: 99%